Selective methylation of toluene using CO(2) and H(2) to para-xylene - Zuo, Jiachang (Sci Adv, 2020)
Toluene methylation with methanol to produce xylene has been widely investigated. A simultaneous side reaction of methanol-to-olefin over zeolites is hard to avoid, resulting in an unsatisfactory methylation efficiency. Here, CO(2) and H(2) replace methanol in toluene methylation over a class of ZnZrO(x)–ZSM-5 (ZZO-Z5) dual-functional catalysts. Results demonstrate that the reactive methylation species (H(3)CO*; * represents a surface species) are generated more easily by CO(2) hydrogenation than by methanol dehydrogenation. Catalytic performance tests on a fixed-bed reactor show that 92.4% xylene selectivity in CO-free products and 70.8% para-xylene selectivity in xylene are obtained on each optimized catalyst. Isotope effects of H(2)/D(2) and CO(2)/(13)CO(2) indicate that xylene product is substantially generated from toluene methylation rather than disproportionation. A mechanism involving generation of reactive methylation species on ZZO by CO(2) hydrogenation and migration of the methylation species to Z5 pore for the toluene methylation to form xylene is proposed.